Assessing the cause of irreversible permeate flux decline of reverse osmosis membranes during the treatment of wastewater. - Rimpelainen, Satu Julia. (University of Ottawa (Canada), 1997)
This study was conducted to determine causes of irreversible permeate flux declines observed during the treatment of waste water. The resistance of reverse osmosis membranes to fouling during the processing of waste water at various crossflow velocities is evaluated. Tests were performed with a three weight percent NaCl solution and with batches of a waste stream that is treated at AECL's Chalk River Laboratories. With the NaCl tests, the mass transfer coefficient of NaCl was determined for crossflows ranging from 30 L/min to 60 L/min. Using the mass transfer coefficients calculated with the NaCl tests, the permeate flux was predicted for the waste stream based strictly on osmotic pressure considerations. A three-step cleaning procedure was developed to restore the permeate flux of the fouled reverse osmosis membranes to an acceptable level of 1 L/min. This level is required in order to prevent accumulation within the process. Tests were also conducted to determine if the three-step cleaning procedure had degraded the integrity of the membrane. (Abstract shortened by UMI.)
Keywords: Engineering, Sanitary and Municipal.